ANALISIS METODE NUMERIK PENGARUH HUJAN TERHADAP KESTABILAN LERENG TUNGGAL TIMBUNAN DI TAMBANG TERBUKA BATUBARA - Akbar, Wahyu Nusantara; Dwinagara, Barlian; Saptono, Singgih; Haq, Shofa Rijalul; Lusantono, Oktarian Wisnu; Prabandaru, Prasodo Datu (Jurnal Teknologi Mineral dan Batubara, 2025)
Indonesia, with its tropical climate and high rainfall, especially near the equator, is prone to slope instability influenced by intense rainfall events. Rainfall increases pore water pressure, reduces effective stress, and decreases shear strength, which in turn lowers the safety factor and increases the probability of failure. However, studies on pore pressure changes during rainfall infiltration have not been extensively studied, particularly in Indonesia. This study aims to analyze the effect of rainfall on the stability of a single slope in a waste dump using a numerical method based on a coupled hydro-mechanical approach. Simulations were conducted using transient finite element analysis (TFEA) to evaluate pore water pressure variations. In addition, the limit equilibrium method (LEM) modeling was also carried out to assess changes in slope safety factors. The analysis was performed using Slide2 software under various rainfall and duration scenarios, with a total of 1,568 model combinations over a 24-hour simulation period. The results show that rainfall events reduce the safety factor value by up to 31.54%. The relationship between the safety factor value and rainfall can be expressed by the equation FK = 2,1607 CH-0,05, which shows a strong correlation with an R2 value of 0,9309.